Comparative functional genomics analysis of cytochrome P450 gene superfamily in wheat and maize - Li, Yixuan (BMC Plant Biol, 2020)
BACKGROUND: The cytochrome P450s (CYP450s) as the largest enzyme family of plant metabolism participate in various physiological processes, whereas no study has demonstrated interest in comprehensive comparison of the genes in wheat and maize. Genome-wide survey, characterization and comparison of wheat and maize CYP450 gene superfamily are useful for genetic manipulation of the Gramineae crops. RESULTS: In total, 1285 and 263 full-length CYP450s were identified in wheat and maize, respectively. According to standard nomenclature, wheat CYP450s (TaCYP450s) were categorized into 45 families, while maize CYP450s (ZmCYP450s) into 43 families. A comprehensive analysis of wheat and maize CYP450s, involved in functional domains, conserved motifs, phylogeny, gene structures, chromosome locations and duplicated events was performed. The result showed that each family/subfamily in both species exhibited characteristic features, suggesting their phylogenetic relationship and the potential divergence in their functions. Functional divergence analysis at the amino acid level of representative clans CYP51, CYP74 and CYP97 in wheat, maize and rice identified some critical amino acid sites that are responsible for functional divergence of a gene family. Expression profiles of Ta-, ZmCYP450s were investigated using RNA-seq data, which contribute to infer the potential functions of the genes during development and stress responses. We found in both species CYP450s had preferential expression in specific tissues, and many tissue-specific genes were identified. Under water-deficit condition, 82 and 39 significantly differentially expressed CYP450s were respectively detected in wheat and maize. These genes may have some roles in protecting plants against drought damage. Thereinto, fourteen CYP450s were selected to validate their expression level through qRT-PCR. To further elucidating molecular mechanisms of CYP450 action, gene co-expression network was constructed. In total, 477 TaCYP450s were distributed in 22 co-expression modules, and some co-expressed genes that likely take part in the same biochemical pathway were identified. For instance, the expression of TaCYP74A98_4D was highly correlated with TaLOX9, TaLOX36, TaLOX39, TaLOX44 and TaOPR8, and all of them may be involved in jasmonate (JA) biosynthesis. TaCYP73A201_3A showed coexpression with TaPAL1.25, TaCCoAOMT1.2, TaCOMT.1, TaCCR1.6 and TaLAC5, which probably act in the wheat stem and/or root lignin synthesis pathway. CONCLUSION: Our study first established systematic information about evolutionary relationship, expression pattern and function characterization of CYP450s in wheat and maize.